Pengaruh Kemampuan Teknik Personal, Keterlibatan Pemakai, Pendidikan dan Pelatihan pada Efektivitas Penggunaan Sistem Informasi Akuntansi - Wira Satria, I Gusti Ngurah Wahyu; Asmara Putra, I Nyoman Wijana (E-Jurnal Akuntansi, 2019)
The effectiveness of accounting information systems is very instrumental in determining the success of management to achieve organizational goals and users of  SIA have a major role in the effectiveness of the system. This study to obtain empirical about the effect of personal engineering skills, involvement of users, education and training on effectiveness of SIA. The population used in this study is all employees who work at the Badung District Government Regional Organization. The method of the sample by nonprobability sampling technique with saturated sampling method, so that the respondents in this study amounted to 37 people. The data analysis technique used is multiple linear regression analysis. The test results of this of personal techniques has a positive effect on the effectiveness of accounting information systems, the involvement of users has a positive effect on the effectiveness of accounting information systems, and education and training have a positive effect on the effectiveness of accounting information systems. Keywords: personal engineering skills, user involvement, education and training, effectiveness of accounting information systems